PENGARUH BOOK-TAX DIFFERENCES, VOLATILITAS ARUS KAS, VOLATILITAS PENJUALAN, BESARAN AKRUAL, DAN TINGKAT UTANG TERHADAP PERSISTENSI LABA (Studi Empiris pada Perusahaan Aneka Industri yang terdaftar di BEI tahun 2010-2014) - Anita Rahmadhani; Zulbahridar '; Hariadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research is aimed to examine and find out evidence of the influence of (1) book-tax differences,(2) cash flow volatility, (3) sales volatility, (4) magnitude of accrual, and (5) leverage on earnings persistence. Samples used in this research are various industries company listed in the Indonesia Stock Exchange (BEI) during period 2010-2014. Total samples are 32 companies. The data are collected using purposive sampling method, the analysis of this research employs multiple regression. Result show the permanen differences in book-tax differences not have significant effect on earnings persistence with significant 0,180, and the temporer differences in book-tax differences with significant 0,009, cash flow volatility with significant 0,036 , sales volatility with significant 0,025, magnitude of accrual with significant 0,034, and leverage with significant 0,000 have effect on earnings persistence.Keyword: book-tax differences, volatility, and earning persistence.